(3dZI GdETGQI JhGUd eY GdMjGIs - (3LeYjI CUOGA dQYGjI GdeYGbjf SeYjGs ((3GdGScfOQjI (B[(3eUQ(B]s (3LeYjI CUOGA dQYGjI GdeYGbjf SeYjGs (3eDSSI SGhjQS ddJfejI GdGLJeGYjIs (3GdCcGOejI GdYQHjI ddYdhe hGdJcfhdhLjGs, 2006)
(3jgOa gPG GdcJGH Gdj JOQjS dZI GdETGQI GdNGUI HGdUe ef NdGd efgL eHJcQ jbhe Ydj CSdhH GdMhGQ hGdeMGOKI h GdZhU aj HfjI gPg GddZI dEOQGc eaQOGJgG hWHjYI eOdhdGJgG eJVefI bhGYO dZI GdETGQIeY JhVjM GdJQJjH GdCeKd dJdc GdeaQOGJ OGNd GdLed GdMhGQjI ddZI hGdGTGQIs
11
Keywords: (3GdUes; (3GdUe JYdjes; (3GdUe QYGjIs